Therapeutic Potential of Fresh Pomegranate in the Management of Pulmonary Fibrosis - Alkhatib, Ahed J (PSM Microbiology, 2024)
Lung fibrosis is a progression of lung disease distinguished by gradual scarring and deposition of lung tissue. It is an extremely challenging disease that impacts lung size and function. The development of lung fibrosis is comparable between smokers and non-smokers. There is no proof of a curative treatment. The principal objective of this inquiry was to present a clinical instance of lung fibrosis alongside the outcomes of a one-month treatment intervention involving the ingestion of fresh pomegranate juice. A diagnosis of pulmonary fibrosis was established in a male patient, aged eighteen years. The parents of the patient conveyed their curiosity regarding alternative therapy approaches considering the absence of a potentially curative medication for their son’s condition at this time. It was recommended that an individual consume two 100 ml glasses of pomegranate fresh juice daily for duration of one month. Upon the expiration of one month, chest X-ray imaging revealed that lung fibrosis had been resolved to an almost complete degree. It has been demonstrated that overall consumption of freshly squeezed pomegranate juice mitigates the progression of pulmonary fibrosis.